Impact of baby spinach as a carrier for the development of sustainable probiotics prior to consumption - Xie, Kangkang; Ling, Jiayi; Mishra, Awdhesh Kumar; Farooq, Muhammad Adil; Ahsan, Samreen; Hassan, Sadia; El-Sherbeeny, Ahmed M.; Abukhadra, Mostafa R.; He, Shan; Liu, Huaxia; Zheng, Shengle; Ahmad, Nabeel (Frontiers in Sustainable Food Systems, 2024)
The development of baby spinach as a vehicle to transfer Lactobacillus plantarum 299v (LP299v) and Lactobacillus rhamnosus GG (LGG) is quite promising and may address the research regarding the absence of suitable whole vegetable carriers in the current probiotic food industry. The objective of this study was to observe the effects of food storage and preparation on Lp299v and LGG viability in baby spinach before consumption. The strains were sequentially introduced into baby spinach by dipping leaves in probiotic suspension to achieve an attachment of approximately 8 log 10 CFU/g spinach. Then, probiotic viability was tested using serial dilutions. Furthermore, data processing and analysis of variance (ANOVA) during 7-day storage with or without salad dressing was performed with Tukey's test. In 7-day storage trials, LP299v and LGG viability on baby spinach declined after 7 days with significant differences by 0.19 log10 CFU/g and 0.39 log10 CFU/g respectively. In salad dressing trials, LP299v (P-Value=0.79>0.05) and LGG (P-Value=0.58>0.05) survivability on baby spinach after the addition of salad dressing fluctuated around 8.27 log10 CFU/g and 8.40 log10 CFU/g with no statistically significant difference respectively. LP299V and LGG viability on baby spinach in both trials was greater than 8 log10 CFU/g and close to FDA requirements, showing that food storage and preparation do not affect their viability and can be used commercially.